Does Information-Processing Cost Affect Firm-Specific Information Acquisition? Evidence from XBRL Adoption - Dong, Yi; Li, Oliver Zhen; Lin, Yupeng; Ni, Chenkai (Journal of Financial and Quantitative Analysis, 2016)
Abstract We examine how information-processing cost affects investors’ acquisition of firm-specific information using a natural experiment resulting from a recent mandate requiring U.S. firms to adopt eXtensible Business Reporting Language (XBRL) when submitting filings to the U.S. Securities and Exchange Commission (SEC). XBRL filings make financial data standardized, tagged, and machine readable. We find that XBRL adoption reduces firms’ stock return synchronicity. The reduction in synchronicity mainly applies to filings under the mandatory program as opposed to the voluntary program. Furthermore, such an effect is more pronounced for opaque and complex firms. Finally, we find that XBRL adoption also reduces price delay.